Incidence of COVID-19 and Its Correlation between Temperature and Population Density - Dan, Siddhartha; Sharma, Deepshikha; Mandal, Mahasweta; Sharma, Deepti (International Journal of Scientific Research in Biological Sciences, 2020)
Meteorological parameters are the important factors influencing the infectious diseases such as SARS and influenza. A study of the prevalence of COVID-19 for each country as a function of temperature was used to define significant differences in temperature and relative humidity. The number of deaths caused by COVID-19, the meteorological parameters and geographical region data were collected from 28th March 2020 to 7th April 2020 worldwide. The correlation of population, population density, and temperature in cities where COVID-19 outbreaks are already becoming epidemics was studied. Generalized additive model was applied to explore the effect of temperature, humidity and population density with the number of cases confirmed, recovered and number of deaths of COVID-19. Worldwide, there were 7,52,394 confirmed, 5,23,480 actives, 1,50,732 recovered and 36,196 death cases due to COVID-19 confirmed. In the duration of case study, the range of the temperature was varied from -7°C to 37 °C. In Mongolia, where temperature range was about -6°C to 1°C, 14 cases were confirmed from the 32,78,290 population and in Burkina Faso, where temperature range was 27 °C to 37 °C, 214 cases were confirmed from the 2,09,03,273 population. USA, a very large area, has different temperature range in different states. For example, in Gaum, USA, there were 56 confirmed cases found in spite of the average temperature of 29°C and humidity 72%, whereas in Alaska, USA, with average temperature of -3°C and humidity 28%, there were found 102 confirmed cases. In summary, this study suggests that the temperature variation and humidity may not be the important factors affecting the COVID-19 mortality.